2014
DOI: 10.1111/jai.12565
|View full text |Cite
|
Sign up to set email alerts
|

Toxicity of smelter slag-contaminated sediments from Upper Lake Roosevelt and associated metals to early life stage White Sturgeon (Acipenser transmontanus Richardson, 1836)

Abstract: The toxicity of five smelter slag-contaminated sediments from the upper Columbia River and metals associated with those slags (cadmium, copper, zinc) was evaluated in 96-h exposures of White Sturgeon (Acipenser transmontanus Richardson, 1836) at 8 and 30 days post-hatch. Leachates prepared from slag-contaminated sediments were evaluated for toxicity. Leachates yielded a maximum aqueous copper concentration of 11.8 lg L À1 observed in sediment collected at Dead Man's Eddy (DME), the sampling site nearest the sm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
6
0

Year Published

2016
2016
2019
2019

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 24 publications
0
6
0
Order By: Relevance
“…Lethal concentrations for most life stage‐contaminant concentrations are above current water quality criteria (Vardy et al., ). However, sublethal effects such as altered movement, diminished hiding, and loss of equilibrium were detected at contaminant concentrations substantially lower than lethal concentrations (Calfee et al., ; Little et al., ; Wang et al., ). Sublethal effects may be more ecologically relevant as elevated mortality would be expected when swimming and hiding is compromised.…”
Section: Conservation Issuesmentioning
confidence: 99%
See 1 more Smart Citation
“…Lethal concentrations for most life stage‐contaminant concentrations are above current water quality criteria (Vardy et al., ). However, sublethal effects such as altered movement, diminished hiding, and loss of equilibrium were detected at contaminant concentrations substantially lower than lethal concentrations (Calfee et al., ; Little et al., ; Wang et al., ). Sublethal effects may be more ecologically relevant as elevated mortality would be expected when swimming and hiding is compromised.…”
Section: Conservation Issuesmentioning
confidence: 99%
“…Site specific contaminant studies found that interstitial pore water from slag substrates collected from the Columbia River were above effect thresholds for WS (Vardy et al., ); however, ambient water quality (i.e., in the water column overlying substrates) did not increase mortality up to 60 days post fertilization (Tompsett et al., ; Vardy et al., ). When exposed to sediment containing slag obtained from the upper Columbia River and leachate prepared from upper Columbia River sediment, abnormal behaviors including immobilization and loss of equilibrium were observed among WS larvae during lab studies (Little et al., ). In addition, when presented with slag‐contaminated sediments, WS larvae remained in close contact to the sediment versus occupying the water column when substrate was not available.…”
Section: Conservation Issuesmentioning
confidence: 99%
“…In previous studies, adverse behavioral responses were evident with early onset during the first few days of acute and chronic exposures to copper and became progressively more severe over exposure duration and concentration 7,8,9 . The magnitude and timing of the onset of these behavioral responses are likely sufficient to limit long-term survival and thus are of concern given the implications for recruitment failure 10 .…”
Section: Introductionmentioning
confidence: 89%
“…effects of heavy metals have been hypothesized / proven as possible / contributing factors for decline of sturgeon population anywhere in the world. Until now studies were done using the acute (96-h) and chronic toxicity tests for: copper (Cu), cadmium (Cd), zinc (Zn), and lead (Pb), in a family member of A. ruthenus, namely the white sturgeon (Acipenser transmontanus) enlisted also as threatened species in Canada and the United States (Calfee et al, 2014;Little et al, 2012Little et al, , 2014Vardy et al, 2014;Wang et al, 2014).…”
Section: Introductionmentioning
confidence: 99%
“…In sturgeons lead and other aquatic pollutants certainly accumulate (Little et al, 2014;Raskovic et al, 2015;Subotic et al, 2013) affecting the spermatozoa quality (Linhartova et al, 2015) or generating adverse behavioral changes (Vardy et al, 2014;Wang et al, 2014).…”
Section: Introductionmentioning
confidence: 99%